Analisis Kelayakan Investasi Perluasan Pabrik dengan Metode Cost-Volume-Profit dan Incremental pada PT XYZ, Jakarta - Jonny Jonny (ComTech: Computer, Mathematics and Engineering Applications, 2012)
PT XYZ received an offer of toll manufacturing services from its client as much as 360 units at a price of Rp14.000 for four years. To be able to fulfill the offer, the company must issue an investment of Rp1,3 billion for the plant expansion regarding to the limited capacity and specificity of the engine that must be purchased separately. There is also some additional operational cost for the company. Based on the analysis of costvolume-profit (CVP) the company realized that the price offered is far below the desired corporate profit by 27% so that the new price agreed upon in the negotiation is Rp16.000. Meanwhile, using the price agreement and macroeconomic assumption for the next four years, the company can finally concluded to accept the offer of its client with a value weighted NPV up to Rp306, 5 million based on the incremental analysis.